A rare encounter mucolipidosis type II alpha/beta: a case report - Anwar, Khadija; Kumar, Darshan (Journal of the Pakistan Medical Association, 2026)
Mucolipidosis type II alpha/beta (ML II) (OMIM # 252500), alternatively referred to as Inclusion Cell (I-cell) Disease, is a relatively rare lysosomal storage disorder that is autosomal recessive in inheritance due to the mutation of the GNPTAB (N-acetylglucosamine-1-phosphate transferase sub-units alpha and beta) gene present on chromosome 12q23.3. Currently, there is no cure for this disorder; treatment is both symptomatic and palliative. This report describes the case of a five-year-old patient with ML II with pathogenic variant (t c.3335+1G>A) who presented with aspiration pneumonia and renal insufficiency. The child was born to a consanguineous couple and had a sibling with a similar clinical presentation who passed away at age four due to cardiovascular complications. The patient was treated with continuous positive airway pressure (CPAP) and IV Tazobactam, Piperacillin, and Vancomycin. On follow-up, she was started on Spironolactone 20mg and Captopril 12.5mg daily for mitral regurgitation. Keywords: Mucolipidosis Type II alpha/beta, Inclusion cell (I-cell) disease, Mitral regurgitation, Clinical homozygosity, Case report.